2014
DOI: 10.1039/c4dt00365a
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the mechanism of selective gate-driven diffusion of CO2 over N2 in MFU-4 metal–organic framework

Abstract: The metal-organic framework MFU-4 shows preferential adsorption of CO2 over N2. This cannot be explained in terms of pore size only. Computational modelling suggests that the unique structure and flexibility of its small 8Cl-cube pore shows a unique gate-diffusion behaviour with different responses to CO2 and N2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 36 publications
5
22
1
Order By: Relevance
“…15). This value is considerably higher as the one determined previously for MFU-4l (16.5 kJ mol −1 ), 22 which is most likely due to the presence of basic amino functions in the tqpt 2− ligand. Alternatively, the increased heat of CO 2 adsorption could also be a special feature of the interpenetrated framework.…”
Section: Gas Sorption Measurementscontrasting
confidence: 68%
“…15). This value is considerably higher as the one determined previously for MFU-4l (16.5 kJ mol −1 ), 22 which is most likely due to the presence of basic amino functions in the tqpt 2− ligand. Alternatively, the increased heat of CO 2 adsorption could also be a special feature of the interpenetrated framework.…”
Section: Gas Sorption Measurementscontrasting
confidence: 68%
“…These counterintuitive results have been unveiled by atomistic molecular dynamics techniques. Using a modified version of the Universal Force Field, 59 we have been able to describe the dynamics of CO 2 penetration in the internal cavities. Thus, when the compartmentalized coordination polymer is completely empty and a low CO 2 pressure is applied, gas molecules start to fill the voids.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on several Zeolitic Imidazolate Frameworks (ZIFs) and COFs have shown that the maximum D 2 /H 2 selectivity is achieved with the ZIF‐8 framework having pores of 3.4 Å diameter, whereas the ZIF‐7 framework with 3.0 Å pores does not show any H 2 or D 2 uptake at all . In contrast, MFU‐4, possessing even smaller pore apertures of 2.5 Å, still shows uptake of both gases due to the flexibility of its narrow pores, which arises from the floppiness of the Cl‐Zn‐N angles, with a very small value of the bending constant (18.5 kcal mol −1 ) as indicated in Table S2, Supporting Information …”
Section: Figurementioning
confidence: 98%
“…[11] In contrast, MFU-4, possessing even smaller pore apertures of 2.5 ,s till shows uptake of both gases due to the flexibility of its narrow pores, which arises from the floppiness of the Cl-Zn-N angles, with av ery small value of the bending constant (18.5 kcal mol À1 )a si ndicated in Ta ble S2, Supporting Information. [33]…”
Section: Experimental Section Experimental Setup Of the Saws Ensormentioning
confidence: 99%